„Kino Wolność wyświetla film produkcji sowieckiej…” – funkcje dolnośląskich afiszy filmowych z lat 1946-1948 w świetle materiałów zachowanych w BUWr - Firlej-Buzon, Aneta (Załącznik Kulturoznawczy, 2024)
The article places the film posters dating from 1946–1948 in the center of attention. Posters belong to ephemeral prints performing specific utilitarian, informational, advertising functions. Original postwar film posters preserved in the Wrocław University Library make it possible to analyze other functions performed by these prints during the period of settlement in the so-called Recovered Territories. The text present the definition of the poster and discusses its features, structure and functions performed by Lower Silesian posters during the analyzed period.